The Influence of Education, Training, and Individual Characteristics on The Performance of Civil Servants in State Administrative Institutions - Lorenta, Meta; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
This study aims to explore the influence of education, training, and individual characteristics on the performance of civil servants within state administration institutions, focusing on a sample of 101 employees randomly selected from the population of 135 at the Jakarta State Administration Institute. This research is included in quantitative research, where the research instrument uses a questionnaire. Utilizing the "Multiple Linear Regression" analysis, the findings reveal nuanced relationships. While education positively correlates with employee performance, the effect is not statistically significant. This non-significant result should be interpreted with caution, emphasizing the need for further exploration and nuanced consideration of the role of education in enhancing performance. Conversely, training exhibits a positive and statistically significant impact on performance, emphasizing its crucial role in bolstering employee effectiveness. Furthermore, individual characteristics have a positive and statistically significant influence on performance. It is essential to convey that the positive effect of education should not be dismissed due to its non-significant nature; rather, it prompts a deeper examination of the intricate dynamics between education and performance. This research underscores the importance of understanding these factors in the context of state administration institutions, providing valuable insights for optimizing the contributions of civil servants and enhancing overall institutional effectiveness.